“Urban-Rural” Dynamics and Indigenous Urbanization: The Case of Inuit Language Use in Ottawa - BUDACH, Gabriele (Journal of Language, Identity & Education, 2014)
peer reviewed The establishment of cities in Canada has played a pivotal role in the displacement, dispossession, and marginalization of Indigenous peoples. Yet, more than half of the Indigenous population now resides in cities, and urbanization continues to increase. This paper addresses a specific aspect of Inuit mobility—namely, migration and the dynamic use of Inuit language and knowledge in the city of Ottawa. Drawing on community-based participatory research in collaboration with an Ottawa Inuit literacy centre, we investigate a range of Inuit-led educational practices that emerged from collaborative work with a group of Inuit women. Suggested activities drew on semiotic resources—including objects and language—that involved retracing the migrational trajectories of Inuit between cities and between nonurban communities, particularly those in their Arctic “homelands.” Such practices appear to cut across the “urban-rural divide,” particularly since cities were rarely mentioned, a fact that seems to signal the irrelevance of this dichotomy for urban Inuit. In this context, the exploration of artifactual literacies—more specifically, speaker interactions that unfold around culturally meaningful objects—led to the following conclusions: (1) multilingual oracy is key to complex transcontextual meaning making; (2) spatiotemporal reference is anchored both in individual experience and in connectivity with members of a newly constituted community; and (3) there is a sharing of cross-generational horizontal knowledge, which includes the abstention from any enforcement of a linguistic norm.